The Role Of Financial Reporting In The Effectiveness Of Management At Pesantren Raudlatul Ulum: Challenges And Innovations - fauzan, Fauzan; Pratiwi, Ana; Mauliyah, Nur Ika (International Journal of Artificial Intelligence Research, 2024)
This study aims to analyze the role of financial reports in enhancing management effectiveness at Pesantren Raudlatul Ulum, as well as to identify challenges and innovations in pesantren financial management. The study employs a qualitative approach with a case study method, involving in-depth interviews with financial managers, the head of the pesantren, as well as observations and analysis of financial report documents. The findings indicate that structured and transparent financial reports play a significant role in supporting strategic decision-making, improving operational efficiency, and strengthening the pesantren's accountability to stakeholders. However, challenges faced include limited human resources, a lack of adoption of modern technology, and the persistence of traditional management cultures. As a solution, the implementation of modern accounting software and staff training in financial management are proposed as innovations that can improve the effectiveness of the pesantren's financial system. This study offers important contributions to pesantren management in the digital era and recommends further research on technology adoption and comparative studies between pesantren